The Influence of Lending Rate on the Performance of Deposit Money banks in Nigeria - Nkamare Stephen Ekpo3, Owui Hycenth Okang Ajaude Edward 2 (International Journal of Scientific Research and Management (IJSRM), 2016)
In a developing economy like Nigeria, the principal reason why banks are licensed is to aid financial intermediation. Banks are expected to support their local environment with adequate supply of credit for all legitimate businesses and consumer financial needs and to ensure that credit is reasonably in line with competitively determined lending rates. Indeed, granting of credit is one of the principal economic functions of banks. Therefore; banks make credits available for consumption and investment spending by business, individual and units of government. They mobilize funds from surplus economic units and then convert such funds as credit facilities to the deficit units. How well a bank performs its lending function has a great deal to do with the economic health of its region, because bank credits support the growth of new businesses and jobs within the banks trading territory and promote economic viability. (Onoh, 2002).                 The process of lending begins from when the credit is granted and managed to make sure that it is judiciously used and within the frame work of the agreement so that it can be repaid back and with interest. Therefore, a bank cannot be too meticulous in taking all the necessary steps to ensure that the loan and advances are given out to worthy Customers. Most banks have failed as a result of non-performing loans which drastically reduces the capital of the banks. This is confirmed with the most recent crisis that took   place in the banking sector of Nigeria in 2009. (Rose, 1996).                 The most widely acknowledged tool for effective credit management is a well articulated and credible loan and credit policy which serves as a guide to all those that handle the management of loans and advances provided to the customers. If good credit management is not instituted, the good loans can turn bad i.e. non-performing credits (Adewumi, 1983). Lending practice depend on a number of varying factors such as the economic environment,  the experience, and expertise of the banker, the  “tradition” and culture of the bank and the personality involved (Rose, 1996). Despite all these a well formulated lending policy should have a general objective and modalities for lending and guideline for credit analysis.                 Reed, Rose, and Pierson (1980), view these factors as the ingredient that determines the lending officer’s faith in the debtor’s ability and willingness to pay the obligation in accordance with the terms of the loan agreement. Many authors call these factors the “six (6) C’s of lending” which are; character, capacity, cash, collateral, conditions, and control. Apart from these principles, there are some other factors and principles which also affect the way banks carry out their lending practices.                Lending which may be on short, medium or long term basis is one of the services that deposit money banks do render to their customers. In other words, banks do grant loans and advances to individuals, business organizations as well as government in order to enable them embark on investment and development activities as a means of aiding their growth in particular or contributing toward the economic development of a nation in general (Felicia,2011). Furthermore non performing loans have been a hindrance to economic stability and growth of economies. In Nigeria, non performing loans continued to improve, underpinned by higher reclassification of  non -performing  loans to performing status and recoveries, as well as efforts to achieve healthier balance sheets via loan write offs.                The rising of non- performing loans has effect on the Deposit money bank; they tightened their lending and switched their attentions to rehabilitating the non performing loans in their books, thus preventing viable businesses from obtainable funds to generate economic activities.   Many studies has been carried out on the area of banking operations but none is relatively done on lending as it affect deposit money banks in Nigeria.              Without prejudice to the requirements of the statement of Accounting standard on Accounting by banks and non bank financial Institutions to be issued by the Nigerian Accounting standards Board in the near future, all licensed banks shall be required to adhere to the prudential guidelines enunciated in this circular for reviewing and reporting their performance. These prudential guidelines should be regarded as minimum requirements and licensed banks which already have more stringent policies and practices are encouraged to continue with them.  It is against this backdrop that the study seeks to observe the influence of lending rate on the performance of deposit money banks in Nigeria.